How Beneficial Is Reduced Graphene Oxide (RGO) for Long-Term Photo Generated Charge Transport in Bismuth Titanate – RGO Nanocomposite Films?. Issue 2 (5th December 2015) - Selvaraj, Josephine; Gupta, Satyajit; Anand, Raghavi; Fiechter, Sebastian; Subramanian, Vaidyanathan (Ravi)
Abstract : This work delineates the results of a systematic analysis of the photoelectrochemical (PEC) and optical responses of reduced graphene oxide (RGO) combined with a representative multi-metal oxide – bismuth titanate (BTO) on films. We investigated the role of RGO as a promoter of charge separation and transport, by suppressing recombination loss of carriers in BTO. The micro-structure of the BTO/RGO composite observed using transmission, scanning electron, and atomic force microscopy, revealed a well-integrated, and highly porous morphology compared to pristine BTO film. The integration of BTO with RGO resulted in a ∼7 fold increase in photocurrent density with an optimal RGO loading of 2 wt%. The performance of the BTO/RGO interface was further examined to obtain critical insights on: (i) how the electrolyte influences the stability of the BTO/RGO composite and (ii) what interactions prevail at the BTO/RGO interface under long-term illumination that impact RGO stability. This work assumes immediate significance because implementation of RGO as a charge transport agent in oxidative systems is currently heavily researched. Unless we can determine a mechanism to protect RGO, its long-term stability, especially under oxidative conditions of any form, must be thoroughly investigated on a case-by-case basis to ensure composite longevity.